Inflation Audit: Optimization of DISDAG Online Application in Market Intervention for Inflation Control From A Shariah Perspective - Sugito, Sugito (PT. ALHAFI BERKAH INDONESIA, 2024)
Inflation is an economic phenomenon that has broad impacts on price stability and the purchasing power of the community. In efforts to mitigate excessive price increases, governments often intervene in the market. One of the instruments used is the DISDAG Online application, which allows real-time and efficient market monitoring. This research aims to evaluate the effectiveness of the DISDAG Online application in optimizing market interventions to control inflation and identify the efforts undertaken by the DISDAG application in market interventions for inflation control. The research method used is descriptive qualitative, with data collection through interviews and literature studies. The results show that the DISDAG Online application has great potential in assisting inflation control through various effective and precise market intervention mechanisms, as well as improving market intervention efficiency by providing broader access to price information and product availability for traders and consumers, thus enhancing ease of access to information and reducing price uncertainty. This research indicates that the implementation of the DISDAG Online application has a positive impact on reducing inflation rates by improving market transparency and efficiency, highlighting the importance of information technology in supporting government policies, especially in the Bojonegoro region, to curb inflation rates.